Planning, performing and analyzing X‐ray Raman scattering experiments. (3rd February 2015) - Sahle, Ch. J.; Mirone, A.; Niskanen, J.; Inkinen, J.; Krisch, M.; Huotari, S.
<x xml:space="preserve">Abstract</x> A compilation of procedures for planning and performing X‐ray Raman scattering (XRS) experiments and analyzing data obtained from them is presented. In particular, it is demonstrated how to predict the overall shape of the spectra, estimate detection limits for dilute samples, and how to normalize the recorded spectra to absolute units. In addition, methods for processing data from multiple‐crystal XRS spectrometers with imaging capability are presented, including a super‐resolution method that can be used for direct tomography using XRS spectra as the contrast. An open‐source software package with these procedures implemented is also made available.